2018
DOI: 10.1002/epi4.12283
|View full text |Cite
|
Sign up to set email alerts
|

Functional seizures: An evaluation of the attitudes of general practitioners local to a tertiary neuroscience service in London

Abstract: Summary Objective Functional seizures are a common functional neurologic disorder. Given their chronic nature, and the biopsychosocial factors involved in their etiology, general practitioners (GPs) play a crucial role in the care of these patients. However, little is known about the attitudes of GPs toward, and knowledge of, functional seizures. Methods The Atkinson Morley Regional Neuroscience Centre in London provides a comprehensive service to patients with functional seizures. As part of a service evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 37 publications
4
15
0
Order By: Relevance
“…For example, consultants have previously reported that they found people with FND more difficult to treat and support (41). Additionally, multiple studies have identified negative perceptions of FND in various healthcare professionals, including neurologists, psychiatrists, GPs, and nurses (18,(42)(43)(44). Lehn et al (38) survey of healthcare practitioners linked these negative perceptions to a fundamental lack of knowledge or misunderstanding of what FND is.…”
Section: Poor Relationships With Healthcare Professionalsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, consultants have previously reported that they found people with FND more difficult to treat and support (41). Additionally, multiple studies have identified negative perceptions of FND in various healthcare professionals, including neurologists, psychiatrists, GPs, and nurses (18,(42)(43)(44). Lehn et al (38) survey of healthcare practitioners linked these negative perceptions to a fundamental lack of knowledge or misunderstanding of what FND is.…”
Section: Poor Relationships With Healthcare Professionalsmentioning
confidence: 99%
“…Further, professionals in primary care settings, such as GPs, are often the facilitators via which specialist management can be accessed, and thus the attitudes and ethical presumptions of these primary care professionals can provide additional barriers in accessing appropriate care. Negative perceptions of patients with FND amongst a variety of healthcare professionals (18)(19)(20) arising from a lack of knowledge about the condition and suspicion of feigning may also impact the extent to which patientcentred care is provided and lead to greater stigmatisation of these patients (21). These barriers may therefore impact on the experience of people with FND as they navigate health systems in order to obtain the help they need.…”
Section: Introductionmentioning
confidence: 99%
“…When presenting the diagnosis of this condition to a patient, a specific and clear label for the seizures should be provided at the beginning of the encounter along with an appropriate description of the condition to the patients and their families 18 . Some authors have already adopted this term (i.e., functional seizures) to describe this condition [28][29][30] .…”
Section: Our Proposal Is "Functional Seizures"mentioning
confidence: 99%
“…Physicians have mixed opinions regarding the etiology of what is called psychogenic seizures [90]. Unfortunately, partial seizure activity that is localized deep within the brain cannot always be measured with the current diagnostic technology that measures seizure activity on the surface of the brain [91].…”
Section: Psychogenic Seizuresmentioning
confidence: 99%